Menstrual Pattern of Reproductive Age Group Women and Their Association with Thyroid Dysfunction - Sughra Abbasi, Amina Bukhari, Sadia Suboohi Sadiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Thyroid hormones play a significant role in physiology of normal reproductive system. Thyroid dysfunction is extremely common in women and effect certain metabolic process and menstrual irregularities. The present study aimed to assess the menstrual pattern of reproductive age group women and their association with thyroid dysfunction. Methodology: This cross-sectional study was carried out on 140 women with menstrual irregularities who were assessed for thyroid dysfunction in the Department of Obstetrics and Gynecology outpatient Department of Sindh Government Hospital Karachi, January 2021 to December 2021. All the reproductive age group women between (15-45 years) with menstrual irregularities were enrolled. Women with a history of thyroid dysfunction and taking anti-thyroid drugs were excluded from the study. Individual age, thyroid hormones level, and type of menstrual irregularities were recorded. ELISA technique was used for the determination of thyroid hormones. Thyroid stimulating hormone (TSH) levels, serum free triiodothyronine (T3), and free thyroxine (T4) were used for the assessment of thyroid dysfunction. SPSS version 25 was used for data analysis. Results: The overall mean age of the study population was 27.8 ± 5.3 years with an age range from 15 years to 45 years. The age-wise distribution of patients were as follows; 15-25 years n=67, (47.8%), 26-35 years n=46 (32.9%), and 36-45 years n=27 (19.3%). The prevalence of thyroid dysfunction was 22% (n=31). The clinical presentations of menstrual patterns were as follows; Irregular menstruation 66.4% (n=93), Oligomenorrhea 4.3% (n=6), Menorrhagia 15.7% (n=22), Polymenorrhea 7.9% (n=11), and Metropathia 6.4% (n=9). Of the total 31 thyroid dysfunction women, the incidence of normal, hypothyroidism and hyperthyroidism was 82 (58.6%), 12 (38.7%) and 1 (1.4%) respectively. The median TSH level was 2 mIU/L IQR (1.0-4.0). The mean level of T3 and T4 was 2.83±1.13 pg/ml and 1.38±1.1 ng/dl respectively. Conclusion: The present study found that hypothyroidism is the most prevalent thyroid dysfunction among women of reproductive age with different menstrual irregularities. The most common clinical presentation was menorrhagia, polymenorrhea, and oligomenorrhea.. Hence the thyroid function evaluation should be mandatory in cases of DUB to detect thyroid dysfunction so the cases have to evaluated for further medical help Keywords: Menstrual Pattern, Reproductive age group women, Thyroid dysfunction